Determinants Of Consumer Decision Making Of A Common Ticketing System In Bangkoks Metropolitan Commuter Transportation Systems - Peerakan Kaewwongwattana; Thepparat Phimolsathien; Paitoon Pimdee (My University, 2015)
The word "commuter" is an American invention. In the 1840s people living in the suburbs could pay a reduced or "commuted" fare to use the trains to get into the cities. The world's worst commute is in Bangkok, Thailand, where people spend about 2 hours a day travelling to and from work. At peak times the average speed of traffic in Bangkok is 7 mph with the total number of vehicles with Bangkok license plates hitting 8.55 million, double the 4.28 registered in 2004. There is hope however as Bangkok during this period has delivered several commuter rail systems. The 15 year old ‘Skytrain’ system has just passed its 2 billionth rider while the 10 year old subway sees 240,000 riders a day. Bangkok’s newest airport ‘rail-link’ system to the suburban international airport while designed for air travelers, has become an access point for suburban commuters. With these three systems however there is no common ticketing system that allows transfer between systems, thus the reason for this paper’s research. Simple Random Sampling was used to obtain questionaries’ from 300 Bangkok commuters in which it was determined that individual decision making has the greatest influence, both directly and indirectly, on the use of a common ticketing system. External variables has the second greatest influence, again both directly and indirectly with a commuter’s personal habits influencing the decision making process in only a limited but direct way.
Keywords: International airport; Transportation Planning and Optimization